Depressive Symptoms and Their Correlates Among Older People in Rural Viet Nam: A Study Highlighting the Role of Family Factors - Trang Thi Hanh Do; Duc Thi Minh Nguyen; Linh Thuy Nguyen (SAGE Publishing, 2022)
This study examined the prevalence of depressive symptoms among older people living in a rural district in Hanoi, Vietnam in 2021. A cross-sectional survey was conducted with a sample of 495 people aged 60 years or older, using a structured questionnaire. The prevalence of self-reported depression, based on the short-form Geriatric Depression Scale-15 items, was 28.7%. Results from multiple variable logistic regression analyses showed that there was a significant association between age, educational level, family support, domestic violence, and depression. The study findings emphasize the importance of screening for depression in older people living in rural areas and the need for interventions aimed to enhance family support and reduce family-related stressors.